Accounting in the system of human capital management at the business entities - Davydiuk, Tetiana; Ostapiuk, Nataliya; Petrenko, Nataliya; Malakhov, Valeriy (Інститут суспільної трансформації, 2015)
Introduction. The world economic experience proves that success of an enterprise depends not only on its material and financial resources, but also on its human capital, which is the basic factor for company’s competitiveness increasing. Effective human capital management based on the data provided by accounting, however, remains underdeveloped. Purpose. Improvement of accounting methodology, which demands a number of techniques and instruments that will enable to implement theoretical assertions, transform the functional contents of business entity’s management. Results. The economic nature of the category of human capital has been proved via adding the properties concerning its structure, conditions of formation and effectiveness of usage, which defines the methodological grounds for including human capital to the accounting system. The directions of cost classification have been offered with reference to human capital theory in terms of human capital components, which is based on its life cycle phases. This provides relevant information arrangement in the necessary analytical terms and encourages accounting methodology development with reference to these costs representation in accounting documentation. The authors propose the directions of improving the theoretical and organizational basis for integrated reporting procedure formation order, which meets the users’ needs in the information concerning the company’s human capital. Conclusion. Amplification of the human capital management paradigm changes the role of accounting in the system of enterprise activity management, it acts as the system of information provision for the enterprise’s human capital management on the basis of systematizing the accounting information on human capital formation, employment and reproduction, which enhances the information capacity of management data and enables decision-making concerning formation and efficient employment of human capital.

У статті проаналізовано роль бухгалтерського обліку в системі управління людським капіталом. Запропоновано класифікацію витрат, виходячи із положень теорії людського капіталу, в розрізі складових людського капіталу, в основу якої покладено фази його життєвого циклу (витрати на формування, використання та відтворення). Авторами обґрунтовано необхідність підвищення інформативності даних шляхом розвитку звітного інформаційного забезпечення системи управління людським капіталом суб'єктів підприємництва для підвищення ефективності подальшого реформування інтегрованої звітності з урахуванням вимог користувачів інформації.
Бухгалтерський облік у системі управління людським капіталом суб'єктів підприємництва
Keywords: human capital; accounting; personnel management costs; sustainable development; integrated reporting; фінансова звітність; бухгалтерський облік; людський капітал; концепція стійкого розвитку; інтегрована звітність